The touch of Madness

Algebra Level 5

( x 9 + 1 x 9 ) + ( x 5 + 1 x 5 ) = 7 ( x 7 + 1 x 7 ) \large \left (x^9+\frac{1}{x^9} \right)+\left(x^5+\frac{1}{x^5}\right)=7\left(x^7+\frac{1}{x^7} \right)

If a complex number x x satisfy the equation above, find the positive value of ( x + 1 x ) \left(x+\dfrac 1 x\right) .

This is one of my original Madness problems .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Ravi Dwivedi
Aug 6, 2015

We note that ( x 7 + 1 x 7 ) ( x 2 + 1 x 2 ) = ( x 9 + 1 x 9 ) + ( x 5 + 1 x 5 ) \large (x^7+ \frac{1}{x^7})(x^2+\frac{1}{x^2})=(x^9+\frac{1}{x^9})+(x^5+\frac{1}{x^5}) =LHS

Using this and the given equation we get

( x 7 + 1 x 7 ) ( x 2 + 1 x 2 ) = 7 ( x 7 + 1 x 7 ) \large (x^7+ \frac{1}{x^7})(x^2+\frac{1}{x^2})=7(x^7+ \frac{1}{x^7})

( x 2 + 1 x 2 ) = 7 \large(x^2+\frac{1}{x^2})=7

( x + 1 x ) 2 2 = 7 \large (x+\frac{1}{x})^2 -2=7

( x + 1 x ) 2 = 9 \large (x+\frac{1}{x})^2=9

( x + 1 x ) = 3 \large (x+\frac{1}{x})=\boxed{3} as only positive value is required

Moderator note:

Great observation with the factorization!

A highly overrated problem

Shreyash Rai - 5 years, 5 months ago

I f S n = ( x n + 1 x n ) , w e h a v e t h e i d e n t i t y . i > j , S i + S j = S ( i + j ) / 2 S ( i j ) / 2 o r S i S j = S i + j + S i j . If~S_n=(x^n+\dfrac 1 {x^n}),~ we~ have~ the~ identity.~~~~i>j,\\ ~\Large \color{#D61F06}{S_i+S_j=S_{(i+j)/2}*S_{(i-j)/2}~~~~~or~~~~~S_i*S_j=S_{i+j}+S_{i-j}.}
In the above i=9, j=5. The rest as above.

Niranjan Khanderia - 3 years, 4 months ago

Let S n = x n + 1 x n S_n=x^n+\frac 1 {x^n}

Note first that S n + 1 = ( x + 1 x ) S n S n 1 = S 1 S n S n 1 , S_{n+1} = \left(x + \dfrac{1}{x}\right)S_{n} - S_{n-1} = S_{1}S_{n} - S_{n-1}, (A).

Thus S 9 = S 1 S 8 S 7 S_{9} = S_{1}S_{8} - S_{7} and S 7 = S 1 S 6 S 5 , S_{7} = S_{1}S_{6} - S_{5}, and so

S 5 + S 9 = S 1 ( S 6 + S 8 ) 2 S 7 . S_{5} + S_{9} = S_{1}(S_{6} + S_{8}) - 2S_{7}.

Since we are given that S 5 + S 9 = 7 S 7 S_{5} + S_{9} = 7S_{7} we see that

S 1 ( S 6 + S 8 ) = 9 S 7 , S_{1}(S_{6} + S_{8}) = 9S_{7}, (B).

But from equation (A) we have that

S 8 = S 1 S 7 S 6 S 6 + S 8 = S 1 S 7 , S_{8} = S_{1}S_{7} - S_{6} \Longrightarrow S_{6} + S_{8} = S_{1}S_{7},

which combined with (B) give us that ( S 1 ) 2 S 7 = 9 S 7 ( S 1 ) 2 = 9 , (S_{1})^{2}S_{7} = 9S_{7} \Longrightarrow (S_{1})^{2} = 9,

since clearly S 7 0. S_{7} \ne 0. The desired positive value of S 1 S_{1} is thus 3 . \boxed{3}.

Can you explain the second line please ? the equation .. (A)

Syed Baqir - 5 years, 10 months ago

Log in to reply

Going from right to left, we have that

S 1 S n S n 1 = ( x + 1 x ) ( x n + 1 x n ) ( x n 1 + 1 x n 1 ) = S_{1}S_{n} - S_{n-1} = \left(x + \dfrac{1}{x}\right)\left(x^{n} + \dfrac{1}{x^{n}}\right) - \left(x^{n-1} + \dfrac{1}{x^{n-1}}\right) =

x n + 1 + 1 x n 1 + x n 1 + 1 x n + 1 ( x n 1 + 1 x n 1 ) = x^{n+1} + \dfrac{1}{x^{n-1}} + x^{n-1} + \dfrac{1}{x^{n+1}} - \left(x^{n-1} + \dfrac{1}{x^{n-1}}\right) =

x n + 1 + 1 x n + 1 = S n + 1 . x^{n+1} + \dfrac{1}{x^{n+1}} = S_{n+1}.

This is a useful general formula for problems of this type.

Brian Charlesworth - 5 years, 10 months ago

Log in to reply

Thanks a lot for teaching this general formula to me and like me.

Niranjan Khanderia - 3 years, 5 months ago
Akhilesh Vibhute
Dec 9, 2015

x=cos∆+isin∆ substitute and simplify you'll get cos∆ as 3/2

Cos cannot have value greater than |1|.

Arghyadeep Chatterjee - 2 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...